MODEL HARMONIZATION OF NORMS OF AIR LAW OF UKRAINE WITH INTERNATIONAL STANDARDS AND PRACTICES - Кузін, С. Г. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
In the article the possible way of harmonization of national legislation with the standards and recommended practices of the International Civil Aviation Organization (ICAO) through model legislation developed within an international program of aviation safety assessment (IASA-International Aviation Safety Assessment).